Artificial Intelligence Technologies as One of The Elements of the Anti-Schoolshooting System - Mikhail Aleksandrovich ZHELUDKOV1; Vladimir Evgenyevich KOVALEVSKY2; Vladislav Eduardovich SUSHCHENKO2 (Communications of International Proceedings, 2021)
Schoolshooting today is a modern type of crime, namely the armed penetration of a person into educational institutions and the commission of mass murder of schoolchildren and teachers, which requires its own scientific understanding and empirical analysis. The active spread of schoolshooting is observed all over the world, since the opportunities for its counteraction are limited by the impact on the psychology of the younger generation and the technical equipment of the security of educational institutions. However, scientific progress does not stand still. All over the world, artificial intelligence programs are used by market leaders to improve public relations, but now we can trace the global trend towards using these technological solutions to control environmental objects in various spheres. This article examines the phenomenon of schoolshooting, taking into account the idea of the nature of such phenomena and the use of facial recognition technologies for its prevention, which have fallen under the influence of this subculture, as well as weapons before committing a crime. The study is based on the identification of two main variables: the technical capabilities of artificial intelligence programs and the ability of law enforcement agencies to respond to schoolshooting in a timely manner. The article shows the problematic moments that have a strong impact on the qualitative use of video surveillance systems in the prevention of schoolshooting in Russia.
Keywords: Schoolshooting; Artificial Intelligence Programs; Digital Environment Law Enforcement Sphere.